Phytochemical Characterization and Bioactivity Evaluation of Extracts Obtained via Ultrasound-Assisted Extraction of Medicinal Plant Phedimus aizoon - Jeongho Lee; Minji Kim; Hyerim Son; Seunghee Kim; Sangjin Jo; Agiimaa Janchiv; Soo-Yong Kim; Taek Lee; Hah Young Yoo (Plants, 2024)
Phedimus aizoon has been utilized as a medicinal plant in Asia. However, the production of phytochemical-rich extracts from P. aizoon and the evaluation of their bioactivity are limited. Herein, phytochemical-rich extracts were prepared by ultrasound-assisted extraction of P. aizoon, with a high extraction yield of 16.56%. The extracts contained about 126 mg of phenolics and 31 mg of flavonoids per g of the extracts. The chromatographic analysis (GC-MS and HPLC analyses) identified 19 notable phytochemicals of the extracts from P. aizoon, including pentacosane, hexadecanoic acid, gallic acid, vanillic acid, and quercetin. The gallic acid content of the extracts was relatively high at 2.75 mg/g. The identified compounds are known to have various bioactivities, such as antioxidant, antibacterial, and antifungal activities. In fact, the prepared extracts exhibited antioxidant activity at 24–28% of that of ascorbic acid. In addition, it showed antibacterial activity against both Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus (Gram-positive bacteria). This study highlights that P. aizoon deserves attention as a natural bioactive substance and emphasizes the need for applications of the extracts from P. aizoon.